Presenting the Model of the Elites' Desertion Factors in Iran's Continental Plateau Oil Company - Mohammad Shaaf Amal; Ahmad Vedadi; Mehdi Tavakoli; Daryoosh Gholamzadeh (مدیریت و چشم انداز آموزش)
Abstract The aim of the current research is to provide a model of the factors of leaving the service of the elites in Iran's continental plateau (Fallaat-e Gharreh) oil company. The research method is applicable in terms of purpose, qualitative in terms of implementation, and a descriptive-survey type. This research is also thematic analysis. The statistical population of this research includes 12 managers of Continental Plateau Oil Company and universities, and the purposeful sampling method was used. Also, in order to collect data,, indicators were extracted by means of content analysis of related backgrounds and the library method, and the research model was extracted through three-step coding. According to the analysis that has been carried out using thematic analysis method to determine the factors of leaving the service of the elites in Continental Plateau Oil Company of Iran, 47 indicators (items), 8 components and 3 dimensions have been identified and confirmed. The results showed that the factors of leaving the service of elites include three organizational dimensions (job nature, management, organizational culture), individual (motivation, demographic characteristics, psychological factors), and environmental (laws and regulations, environmental pressures). Extended abstract Introduction Undoubtedly, human resources are the most important asset of the organization; because human resources in the organization are scarce and irreplaceable resources, and they create economic value and competitive advantage for the organization by the knowledge, skills, and abilities they bring to the organization; therefore, the most important task of human resources management is to create competition in attracting talented and worthy people and maintaining the main human resources in the organization, which is considered as a strong competitive strategy (Amiri & Mahmudzadeh, 2015). In fact, human capital is considered the most valuable and complex capital in any organization, which plays the main role in achieving organizational goals. In the meantime, knowledge workers or elites are workers who are in a high level in terms of knowledge skills and expertise. These people have the ability to observe, combine and interpret data and information to make better decisions and provide more suitable solutions for the organization (Gholipor et al, 2013). Nevertheless, some organizations lose a significant part of their knowledge workers for various reasons, including restrictive requirements and laws, not giving employees freedom of action and excessive control over them, burnout, job plateauing, lack of organizational support, lack of attractiveness, the unfair compensation of services, reducing authority and losing decision-making power (Karimi Taher et al, 2021). In this regard, one of the most important issues of organizations in today's world is the issue of leaving the service of employees, especially skilled employees or talents, which has many negative consequences for organizations. Attrition costs for the organization come from different directions (Piraish et al, 2020). Based on this, the main question of this research is; what are the reasons for leaving the service of the elites in Iran's continental plateau oil company? Theoretical Framework leaving service The problem of absenteeism and desire to leave the service of employees is one of the issues that are of particular interest to managers and researchers these days, so organizations should take measures to identify and solve problems in the stage of wanting to leave service before the act of leaving service, because this problem has negative effects on employee motivation and ill attitude towards other employees (Nornezhad et al, 2020). Since the social and economic well-being and the provision of sufficient facilities to satisfy the material and spiritual needs of the people of the society require that, firstly; the people of the society should be educated morally and socially, and secondly; as much as possible, as many people as possible should acquire knowledge, perception and skills; thirdly, elite and talented people should be cultivated according to their capabilities and abilities; and finally, with education, different groups of society can actively participate in their organization and administration (Mirkamali, 2017). Generally, leaving the service is considered a process that occurs when a person leaves a specific job or organization (Kavousi et al, 2021). Ebrahimi Khabir (2023) investigated the degree of tendency and reasons for leaving the service of employees of organizations in the cities of Tehran province. The results of the research showed that the reasons for leaving the organization were significant. F scores were for 1/306. As a result, it can be stated that for the initial stages of employment and before entering the organization, the characteristics of these jobs as well as the limitations and benefits that exist in them should be explained to the candidates in a correct and realistic manner so that the candidates can imagine an accurate picture of this job in their minds before choosing it, and can make an accurate assessment of the existing realities in areas such as salaries and benefits and amenities, how to promote and advance their careers, and this research is effective for people's choices in the future. Dari (2022) investigated the identification of effective strategies to maintain and prevent personnel leaving the service in Kashmar municipality. In their research, they showed that the most important strategies to prevent personnel from leaving the service and to maintain them in the municipality of Kashmar were determined as follows: Safety and health criteria, rights and benefits criteria, organizational criteria, individual criteria, cultural criteria. Research methodology The research method is applicable in terms of purpose, qualitative in terms of implementation, and a descriptive-survey type. This research is also thematic analysis. The statistical population of this research includes 12 managers of Continental Plateau Oil Company and universities, and the purposeful sampling method was used. Also, in order to collect data,, indicators were extracted by means of content analysis of related backgrounds and the library method, and the research model was extracted through three-step coding. Research findings For analysis, thematic analysis method was used, and the extraction of the components and indicators was obtained from the review of related backgrounds and the library method, and then coding was used for analysis. According to the analysis that has been carried out using thematic analysis method to determine the factors of leaving the service of the elites in Continental Plateau Oil Company of Iran, 47 indicators (items), 8 components, and 3 dimensions have been identified and confirmed. The results showed that the factors of leaving the service of elites include three organizational dimensions (job nature, management, organizational culture), individual (motivation, demographic characteristics, psychological factors), and environmental (laws and regulations, environmental pressures). Conclusion The present study was conducted with the aim of providing a model of elites' leaving service in Iran's continental plateau oil company. The results of this research are in agreement with the results of Ebrahimi Khabir (2023), Dari (2022), Piraish et al, (2020), Kavousi et al, (2021), Kelly et al, (2022), Tetık et al, (2021), and Hadavand (2021). Piraish et al, (2020) showed that there is a significant and direct relationship between the supervisor's characteristics, job characteristics, feelings and emotions in the job, job attitude and working conditions with the reduction of employee turnover and transfer, and the most influential factor is feelings and emotions in the job; and also, job attitude has the least effect on the intention to leave the service and transfer of employees and finally on the efficiency of the company. In line with the results obtained, it is suggested that organizations value many benefits such as social security insurance and provision of retirement resources, bonuses, annual vacation allowances and promotion and career growth opportunities; consider the skills of employees more valuable and also ensure the improvement of their personal quality of life. This allows employees to advance to higher positions and enjoy more job benefits, so they will not take leaving the job seriously and will tend to continue their involvement in the organization for a longer period of time.